Immunogenicity of avelumab in patients with metastatic Merkel cell carcinoma or advanced urothelial carcinoma - Ping Hu; Haiqing Isaac Dai; James Bourdage; Dongli Zhou; Ky Trang; Karey Kowalski; Carlo Bello; Jennifer Hibma; Akash Khandelwal; Kyra Cowan; Jennifer Dong; Karthik Venkatakrishnan; et al. (Wiley, 2024)
Abstract Like other monoclonal antibodies, immune checkpoint inhibitors may be immunogenic in some patients, potentially affecting pharmacokinetics (PKs) and clinical outcomes. In post hoc analyses, we characterized antidrug antibody (ADA) development with avelumab monotherapy in patients with metastatic Merkel cell carcinoma (mMCC) from the JAVELIN Merkel 200 trial (first‐line [1L; N = 116] and second‐line or later [≥2L; N = 88] cohorts) or with advanced urothelial carcinoma (aUC) from the JAVELIN Bladder 100 (1L maintenance [N = 350]) and JAVELIN Solid Tumor (≥2L [N = 249]) trials. Treatment‐emergent ADAs developed in a numerically higher proportion of patients with aUC (1L maintenance, 19.1%; ≥2L, 18.1%) versus mMCC (1L, 8.2%; ≥2L, 8.9%); incidences within tumor types were similar by line of therapy. In PK analyses, numerically lower avelumab trough concentration and higher baseline clearance were observed in treatment‐emergent ADA+ versus ADA− subgroups; however, differences were not clinically relevant. Numerical differences in overall survival, progression‐free survival, or objective response rate by ADA status were observed; however, no clinically meaningful trends were identified. Proportions of patients with treatment‐emergent adverse events (TEAEs; any grade or grade 3/4), serious TEAEs, TEAEs leading to treatment discontinuation, or infusion‐related reactions were similar, with overlapping 80% confidence intervals between ADA subgroups. Efficacy and safety observations were similar in subgroups defined by early development of ADA+ status during treatment. In conclusion, no meaningful differences in PKs, efficacy, and safety were observed between subgroups of avelumab‐treated patients with different ADA status. Overall, these data suggest that ADAs are not relevant for treatment decisions with avelumab.